Penetration of SDF and AgF from the infected dentine towards the unaffected tooth structure - Mulder, Riaan; Potgieter, Nicoline; Noordien, Naeemah (Frontiers in Oral Health, 2023)
The use of SEM-EDS line scan analysis to evaluate the movement of ions from dental materials towards the tooth structure and the concept of ion movement is well established. This analysis technique was used to determine the ion movement of two commercially available silver and fluoride-containing products. Methods: This study aimed to compare the elemental analysis of primary molar teeth treated with Silver Diamine Fluoride (SDF) and Water Based Silver Fluoride (AgF) from the infected dentine towards the healthy dentine. The teeth were cleaned from debris and contaminants off the roots and stored until use. Fifteen primary molars with large active cavitated lesions, not extending into the pulp (specimens) were respectively divided into three test groups: Silver Diamine Fluoride (SDF) (n=5), Water Based Silver Fluoride (AgF) (n=5) and De-ionized Water (W) (n=5) as the control group. Therefore, the infected dentine length of the scan was (22.80μm -8 scan points of 2.85μm apart), and the affected dentine including the healthy dentine was (59.8μm -21 scan points). The SEM-EDS line scan from each specimen determined the average fluoride, iodide and silver weight percentage for that specimen. The samples n=15 SEM-EDS line scans were used to determine the average ion movement in wt%. The Kruskall-Wallis test and the Tukey HSD tests were completed at a p<0.05. SDF and AgF presented no significant fluoride movement in terms of the weight percentage. There was however significantly more fluoride movement from infected caries to the healthy dentine with SDF and AgF (p=0.0010053) compared to the control specimen treated with de-ionized water. There was no significant difference between SDF and AgF for the movement of the iodide (p=0.5953) and silver (p=0.3708) from infected caries to the healthy dentine. Conclusion: SDF and AgF easily penetrated through infected caries, affected tooth structure and to the healthy dentine for the line scan of 82.65μm. There was no significant difference between SDF and AgF for the movement of ions within the infected dentine nor in the affected/healthy dentine.